RESPONSE OF SOYBEANS AND WHEAT TO PHOSPHORUS FERTILIZATION ON CALCAREOUS ALLUVIAL SOIL OF SAVA VALLEY AREA IN BOSNIA AND HERZEGOVINA - Jurica JOVIC; Manda ANTUNOVIC; Mirta RASTIJA; Ivana VARGA (Trakya University Journal of Natural Sciences, 2015)
The stationary field experiment of increasing rates of phosphorus (P) fertilization started in spring 2011 on calcareous alluvial soil of Posavian Canton in Federation of Bosnia and Herzegovina (B&H). The level of plant available P was found to be low by previous soil tests carried on with ammonium-lactate-method (7.06 pH in 1 M KCl; 4.17% organic matter; 3.79% CaCO3; 5.4 mg P2O5 in 100 g of soil). Five rates of P fertilizers (monoammonium phosphate: 13% N + 53 % P2O5) were applied as follows (kg P2O5 ha-1): a = 75 (basic fertilization), b = 225, c = 375, d = 525 and e = 975). The experiment was conducted in four replicates (basic plot 60 m2). Only basic fertilization was applied in the following years. Crop rotation was as follows: soybean (2011) - winter wheat (2012 + 2013). Soybean yield increased for 20% (2.11 and 2.53 t ha-1, respectively) with P fertilization from 75 to 375 kg P2O5 ha-1, whereas further increase of P rates resulted with lower yield compared to the control level. In both years significant differences of wheat yields were found only between basic and each rate of the increased P fertilization. Wheat yields of the control group were 6.21 and 6.44 t ha-1, for the harvest of 2012 and 2013, respectively. P fertilization led to an increase in wheat yields up to 13% in 2012 and 15% in 2013. Mean values of wheat yields of four P treatments (b+c+d+e) were 6.92 and 7.21 t ha-1 for 2012 and 2013, respectively.